Role of Gender, Age, and Family System on Neuroticism, Attachment, and Well-being among Young Adults - Janjua, Maria Muzaffar; Shaukat, Aaisha; Shamim, Farah (Annals of Human and Social Sciences, 2024)
This study focuses on investigating the relationship between personality traits, attachment styles, and psychological well-being in young adults in Pakistan. The research explores the moderating effects of gender, age, and family system on these relationships. The study employed a quantitative approach and a correlational cross-sectional research design. Data was collected using questionnaires from 274 university students aged 18 to 30. The instruments used included the Ten Item Personality Inventory (TIPI) to measure personality traits, the Adult Attachment Scale (AAS) to assess attachment styles, and the Psychological Wellbeing Scale (PWS) to measure psychological well-being. The results showed that gender moderated the relationship between personality traits and adult attachment styles, with females demonstrating a stronger association. Gender also acted as a moderator between neuroticism and close attachment style, buffering the relationship. Age was found to moderate the relationship between neuroticism and self-acceptance, weakening the association as individuals grew older. The family system, particularly joint family systems, was found to moderate the relationship between neuroticism and personal growth, strengthening the association. These findings have implications for understanding and promoting psychological well-being in young adults and highlight the importance of considering gender, age, and family system in psychological research and interventions.